EFL Students’ Perspective of Using Whatsapp as Learning Media in Covid 19 Situation - Nurasmi Panigfat; Adi F. Mahmud (EDU Journal - English Department of UMMU Journal, 2021)
Learning not only take place in the classroom manually but also it can be done through online. Online learning needs a platform or a media to connect teacher and students or students and students such as; Zoom Meeting, Google Classroom, Facebook, IG, and Whatsapp. Wahtsapp is one of social media which used to send messages, voice calls, and video calls both individually and groups. This research attempts to explore EFL students' perspective of using whatsapp as learning media in Covid 19 situation. Descriptive qualitative design was applied to do this research. The research subjects were EFL students of English Department of Muhammadiyah University of North Maluku. They were in the third semester who consisted of 11 students. The research data were collected by using questionnaire and interviewed. Data from questionnare analyzed through descreptive statistic by using microsoft excel while interview data analyzed by following three steps; data reduction, data presentation and data conclusion. The results of research showed EFL students' have positive perspective toward whatsapp as learning media. It was proven the everage percentage of students from questionnaire more than 50% (64.7%). Basides, EFL students’ responses through interview support positively the results from questionnaire.